2016
DOI: 10.1007/s11606-016-3685-3
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing Improves Medication Adherence: a Systematic Review and Meta-analysis

Abstract: BACKGROUND: Randomized clinical trials (RCTs), mostly conducted among minority populations, have reported that motivational interviewing (MI) can improve medication adherence. OBJECTIVES: To evaluate the impact of MI and of the MI delivery format, fidelity assessment, fidelity-based feedback, counselors' background and MI exposure time on adherence. DATA SOURCES: We searched the MEDLINE database for studies published from 1966 until February 2015. STUDY ELIGIBILITY CRITERIA: We included RCTs that compared MI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
106
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 45 publications
8
106
0
2
Order By: Relevance
“…Motivational interviewing has previously been used to enhance adherence with medical therapies and psychotherapy, resulting in improved patient outcomes, in patient populations with high rates of ambivalence and nonadherence . Similarly, our prior observational study of patients with PNES has shown that there is an association between adherence with psychotherapy and improved outcomes .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Motivational interviewing has previously been used to enhance adherence with medical therapies and psychotherapy, resulting in improved patient outcomes, in patient populations with high rates of ambivalence and nonadherence . Similarly, our prior observational study of patients with PNES has shown that there is an association between adherence with psychotherapy and improved outcomes .…”
Section: Discussionmentioning
confidence: 93%
“…Motivational interviewing (MI) is a patient‐oriented counseling style that was developed to address the problem of ambivalence about behavioral change . MI has been shown to be effective in improving patient engagement and adherence with numerous medical treatments and psychotherapy in a number of medical and psychiatric conditions, although never in PNES or other functional neurological disorders …”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated the effectiveness of motivational interviewing for patients with a variety of conditions, such as attention deficit/hyperactivity disorder, obesity, medication adherence, human immunodeficiency virus, and alcohol misuse . First, it is crucial to understand the underlying spirit or mindset of motivational interviewing and to master the core skills, as shown in Figure , through by repeated simulation trainings and audio or video recordings with feedback learning.…”
Section: Discussionmentioning
confidence: 99%
“…MI is associated with better adherence to medications (6), higher rates of successful smoking cessation (7), and increased physical activity (8). Given this evidence, we previously hypothesized that MI would promote and help maintain adherence to an exercise prescription.…”
Section: Introductionmentioning
confidence: 99%